2016
DOI: 10.1002/adem.201500645
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Explanation for the Large Difference in Improving Shape Memory Effect of Fe–Mn Alloys by Co and Si Addition

Abstract: The authors investigate the shape memory effect (SME) and microstructure evolution of the Fe-25Mn, Fe-25Mn-6Co, and Fe-25Mn-6Si alloys before and after deformation at room temperature (RT) through ex situ optical observation. After deformation, the stress-induced reverse transformation of thermal e martensite, an unrecovered deformation mode, can be easily observed in the Fe-25Mn and Fe-25Mn-6Co alloys, but it can be hardly observed in the Fe-25Mn-6Si alloy. The lower values of chemical driving force for e ! g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recently, based on thermodynamic calculated results, Chen et al revealed that Si can remarkably increase the chemical driving force of FCC → HCP martensitic transformation at RT, but Co cannot do that, as shown in Figure c . The reason is that Si exhibits a stronger capability of lowering the T N temperature than Co. Consequently, Si addition can remarkably reduce magnetic free energy difference (Figure b).…”
Section: Role Of Si In Achieving Large Recovery Strains In Fe–mn–si‐bmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, based on thermodynamic calculated results, Chen et al revealed that Si can remarkably increase the chemical driving force of FCC → HCP martensitic transformation at RT, but Co cannot do that, as shown in Figure c . The reason is that Si exhibits a stronger capability of lowering the T N temperature than Co. Consequently, Si addition can remarkably reduce magnetic free energy difference (Figure b).…”
Section: Role Of Si In Achieving Large Recovery Strains In Fe–mn–si‐bmentioning
confidence: 99%
“…The reason is that Si exhibits a stronger capability of lowering the T N temperature than Co. Consequently, Si addition can remarkably reduce magnetic free energy difference (Figure b). As the result of the lower chemical driving force of FCC → HCP martensitic transformation at RT, an unrecovered deformation mode, that is, the stress‐induced reverse martensitic transformation of thermally‐induced HCP martensite, took place in Fe–25Mn and Fe–25Mn–6Co alloys, when deformed at RT . By contrast, it was difficult for the occurrence of stress‐induced reverse martensitic transformation of thermally‐induced HCP martensite in a Fe–25Mn–6Si alloy .…”
Section: Role Of Si In Achieving Large Recovery Strains In Fe–mn–si‐bmentioning
confidence: 99%
See 3 more Smart Citations